2018
DOI: 10.4236/aad.2018.74009
|View full text |Cite
|
Sign up to set email alerts
|

Arginase as a Potential Target in the Treatment of Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is a slowly progressive, neurodegenerative disorder with an insidious onset that is characterized by severe decline in memory, thinking and reasoning skills. Advanced age is a prominent risk factor for AD and other metabolic diseases, such as type II diabetes and atherosclerosis. Their causal mechanisms are multifaceted and not fully understood. The precise pathophysiology of AD remains a mystery despite decades of intensive investigation. Thus far, there is no truly successful AD ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 110 publications
0
20
0
Order By: Relevance
“…ARG2 activation is a leading factor of atherosclerotic vascular disease development [52], and diabetic renal injury [53]. Accordingly, arginase inhibition has been suggested to be a promising therapeutic strategy [20,54,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ARG2 activation is a leading factor of atherosclerotic vascular disease development [52], and diabetic renal injury [53]. Accordingly, arginase inhibition has been suggested to be a promising therapeutic strategy [20,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…However, the decline in substrate bioavailability and/or activation of arginase leads to a substantial shift of the balance toward ornithine synthesis ( Figure 1b). It seems that arginase activation is a conserved evolutionary reaction to various stimuli [20].…”
Section: Introductionmentioning
confidence: 99%
“…Brain arginine deprivation, due to arginase over-activation, has been suggested as a cause of AD [12]. Consequently, arginine supplementation [13] and/or arginase inhibition have been proposed to halt AD development [14], and have been successfully tested in AD mice [15]. Of note, non-proteinogenic unbranched-chain amino acid norvaline was shown to amplify the NO levels and reduce urea production and it has been used successfully to treat artificial metabolic syndrome in rats.…”
mentioning
confidence: 99%
“…These authors demonstrated that NOS1 repression decreases neuronal differentiation, and vice versa, NOS1 upregulation promotes it.The semi-essential amino acid, arginine, is a mutual substrate for both NOS and arginase. Brain arginine deprivation, due to arginase over-activation, has been suggested as a cause of AD [12].Consequently, arginine supplementation [13] and/or arginase inhibition have been proposed to halt AD development [14], and have been successfully tested in AD mice [15]. Previously, we showed that arginase inhibition with norvaline upsurges the hippocampal levels of NOS3 [16], and NOS1[17] in AD model mice.Additionally, our advanced proteomics assay revealed that chronic treatment of 3×Tg mice with norvaline led to the activation of several critical for adult neurogenesis biological processes [15].One of the most significant pathways detected was the neuregulin (NRG) pathway.…”
mentioning
confidence: 99%
“…Consequently, arginine supplementation [13] and/or arginase inhibition have been proposed to halt AD development [14], and have been successfully tested in AD mice [15]. Previously, we showed that arginase inhibition with norvaline upsurges the hippocampal levels of NOS3 [16], and NOS1…”
mentioning
confidence: 99%